Effects of Various Processing Methods on the Ultrastructure of Tendon Collagen Fibrils from Qinchuan Beef Cattle Observed with Atomic Force Microscopy - Guixia Li; Yunfei Wan; Xuan Song; Ying Wang; Linsen Zan; Jie Zhu (Journal of Food Quality)
Atomic force microscopy was utilized to study the effects of ultrasound oscillation, microwave heating, water bath cooking, and acid-base soaking on the ultrastructure of collagen fibrils of Qinchuan beef cattle tendons. D-spacing length and roughness of collagen fibrils always showed a 1.02% increment in the group which was processed for 20 min rather than for 10 min under different ultrasound frequencies. Microwave heating had a slight impact on D-spacing length and roughness at lower power (140–560 W), and collagen fibrils always showed a 1.02% increment for 20 min. Then, visible changes were noted with increasing power and time. D-spacing length reduced by 1.01% at 50°C for treatment periods of 10 min, 20 min, and 30 min, and there was no obvious change at 60°C; the periodic structure disappeared after cooking for 20 min, when fibrils had become gelatinized at 70°C. Collagen fibrils became disorganized at pH 3, following acid-base soaking. The present study indicated that acid-base soaking had an outstanding effect on the ultrastructure of collagen fibrils, especially in an acidic environment in consideration of the special structure of collagen.